Body image and emotional distress in newly diagnosed cancer patients: The mediating role of dysfunctional attitudes and rumination. (March 2017) - Liu, Jianlin; Peh, Chao Xu; Mahendran, Rathi
Highlights: BIC is associated with emotional distress for cancers across various sites. Few studies examined cognitive risk mechanisms linking BIC and emotional distress. Path analysis was used to examine the hypothesized mediation model. Dysfunctional attitudes and rumination linked BIC and emotional distress. Interventions are needed to address BIC, dysfunctional attitudes, and rumination. Abstract: Body image concerns (BIC) has been reported to be associated with emotional distress for cancers across various sites. This study sought to examine two cognitive vulnerability mechanisms: dysfunctional attitudes and rumination, and their combined effects on the relationship between BIC and emotional distress in newly diagnosed Asian cancer patients. Participants were 221 newly diagnosed adult cancer patients who were assessed on BIC, rumination, dysfunctional attitudes, and emotional distress. Path analysis was used to examine the hypothesized mediation model. The hypothesized mediation model controlling for age, sex, marital status, education level, cancer type, cancer stage, and treatment modality revealed that both dysfunctional attitudes and rumination mediated the relationship between BIC and emotional distress. The present study provides evidence for a mediating role of dysfunctional attitudes and rumination between BIC and emotional distress. Psychological treatment should target dysfunctional attitudes and rumination in cancer patients experiencing BIC.